CAPACITY BUILDING OF CIBULEO TOURISM VILLAGE COMMUNITY IN DEVELOPING FEATURED PRODUCTS USING E-COMMERCE - Herawati, Susetya; Wahyono, Herry; Padmono Putro, Harjono (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2023)
This study is a research program conducted by Universitas Krisnadwipaya in Cibuleo TuguUtara Tourism Village, which aims to help the Cibuleo Tugu Utara Tourism Village community inincreasing the excellence of their local products through the e-commerce (electronic commerce) systemas a form of a new method phenomenon that provides modern business infrastructure through the internet. Tourism village development may take place through 4 (four) criterias: something to see, something to do, something to buy and something to learn. And this requires creativity and innovationfrom the village community. The role and availability of human resources is also very important inrealizing and improving the development of tourist villages. Therefore, one of the creativity andinnovation that can be done in this digital era is to build a modern business infrastructure through theinternet. Promotional media is very important for tourism village management in communicatingbusiness marketing of coffee planting and processing, village culinary, village tourismobjects andattractions. Thus, the purpose of using and utilizing internet media is to be able to help and facilitate (efficiently and effectively) in providing exposure to village tourism products and services for the wider community to encourage them to use this convenience regardless of space and time. The researchmethod uses a qualitative method with an Interactive Model popularized by Miles, Huberman andSaldana (2014). The results of the study recommend the e-commerce digital marketing model. Keyword: E-commerce, Human Resources, Tourism Village, Tugu Utara, Cibuleo.